Efisiensi Saluran Pemasaran Buah Salak (Salacca zalacca) di Dusun Kendalan Desa Semboro Kabupaten Jember - Solihah, Imroatus; Kurniawan, Deddy (KUBIS, 2023)
Marketing snake fruit does not require special techniques, but it still requires attention, as is the case in Kendalan Hamlet. However, the lack of marketing channel information and lack of knowledge about it means that people pay less attention to the efficiency of the business. The aim of this research is to determine the marketing channels for salak, the marketing efficiency of salak in Kendalan Hamlet, Semboro Village, Semboro District, Jember Regency. The research method used is marketing efficiency analysis. The results and discussion show that the marketing channel pattern used in Kendalan Hamlet, Semboro District, Jember Regency uses two types of salak marketing channels, a) Marketing channel I: salak farmers/producers - traders - final consumers. b) Marketing channel II: salak farmers/producers – traders I – Traders II - final consumers. Marketing channel pattern I with an efficient value of 7.03%, and marketing channel II with an efficient value of 13.05%. It can be concluded that marketing channel I with a value of 7.03% is more efficiently used as a marketing channel for salak in Kendalan Hamlet, Semboro District.